Total productive maintenance (TPM) implementation based on lean manufacturing tools in Indonesian manufacturing industries - Adesta, Erry Yulian Triblas; Prabowo, Herry Agung (Science Publishing Corporation Inc, 2018)
Only a few companies in Indonesia have implemented Total Productive Maintenance (TPM) and Lean Manufacturing (LM) properly. They also implemented LM separately with TPM. To look beyond their implementation, a research through survey method will be conducted to identify the status of TPM and LM practices. The data recorded through the survey will be calculated and analysed using Structural Equation Modelling (SEM) with Smart-PLS as a programming tool. The expected results were to provide updated barriers and enablers factors in implementing TPM and LM, to produced reliable CFA (measurement) models for TPM, LM and MP and proposing reference model (structural model) of the relationship between TPM, LM, and MP for manufacturing industries in Indonesia.